Factors Associated With Myopia Incidence at Regional General Hospital DR. Adnaan WD Payakumbuh Year2017 - Gustin, Rahmi Kurnia; Andiny, Saskia (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
Myopia or nearsightedness is a form of the refractive disorder that can cause blindness. The prevalence of myopia has been reported to be as high as 70% -90% in some Asian countries, 30% -40% in Europe and the United States and 10% -20% in Africa. Survey of the Ministry of Health of the Republic of Indonesia 1993-1996 obtains refractive abnormalities in Indonesia of 24.72% ranks first in 10 most eye diseases. The case of myopia in RSUD Dr. Adnaan WD Payakumbuh as many as 725 people. This study aims to determine the factors associated with the incidence of myopia in RSUD Dr. Adnaan WD Payakumbuh. Research type using analytic study with cross-sectional approach. The research was conducted at Poli Mata RSUD Dr. Adnaan WD Payakumbuh in April to September Year 2017. The population of this study was all patients who visited the Eye Poly RSUD Dr.Adnaan WD Payakumbuh Year 2016 as many as 725 people. Sampling using non-random sampling technique (Nonprobability) with the number of 88 people.Data collection using doctoral questionnaires and diagnosis. The data analysis result of research includes univariate and bivariate analysis using the chi-square test. The results obtained from 88 respondents as many as 48 respondents (54.5%) myopia, 52 respondents (59.1%) age are not at risk, 54 respondents (61.4%) have a history of myopia and 7 respondents (8.0%) close looking activity is quite heavyÂ The result of age analysis with myopia occurrence obtained p-value = 0,000, Family History with myopia incidence obtained p-value = 0.000 and Activity View With the occurrence of myopia obtained p-value = 0.000. It can be concluded that age, family history and near seeing activity have a connection with the incidence of myopia. It can be concluded that age, family history, and near looking activity are statistically related to the incidence of myopia. It is recommended to all people to avoid bad habits and always check eye health to the doctor.